Sustainable Tourism Concept to Revitalize Ocarina Area in Batam City, Indonesia - Helen Cia; I Gusti Ngurah Anom Gunawan; Hendro Murtiono (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2020)
The purpose of this research is to explore the concept of revitalizing the coastal tourism area with a sustainable tourism approach. Ocarina area is one of the tourist destinations in Batam city. Its strategic location is right in the center of Batam and is surrounded by several areas with different functions, among others there are housing (housing Regata, housing Monde Residence, housing Avante, Monde Signature housing, etc.), a school (Mondial school), a commercial area ( Pasir Putih shops, Mahkota Raya shops) and also the location of Ocarina area is close to the international ferry. The phenomenon that occurs in this tourist area has long been built and managed but has decreased visitors so that needs to be revitalized by using the concept of sustainable tourism. This strategic location is not accompanied by the success of the development of the Ocarina area as a public space that offers a variety of game facilities and culinary venues. The phenomenon that makes the need for revitalizing measures both physically and economically to make the Ocarina area can attract visitors to come and enjoy the facilities that are in it. The research method was a qualitative method of direct observation in the field. Analysis process is conducted to identify the problems that exist in the field today especially in the area of Ocarina Phase 1 so that the area of Ocarina Phase 2 can make Ocarina Phase 1 to be revitalized area and can be one of the sustainable tourism Batam city that can improve the economy of Batam city. Keywords: revitalization, sustainable tourism, visitor